The Scavenger Hunt: A Technique for Enhancing Culture Learning and Intercultural Communication Practice - Martha Nandari Santoso (UIN Salatiga, 2020)
In this changing era, which is characterized by the interconnected world, and the increasing mobility of people, the need to be able to communicate inter-culturally is evident. To be successful in intercultural communication, one does not only need to be linguistically competent but also culturally knowledgeable and sensitive. Bearing in mind these cultural needs, this paper details the scavenger hunt technique as a tool for enhancing culture learning and intercultural communication practice. Although this technique applies to students of any major, this study was specifically implemented to a group of English as a Foreign Language (EFL) students in Indonesia. Participants of this study were nine (9) male and twenty (20) female students of The English Language Education Program at a private university in Central Java, Indonesia. The students did the scavenger hunt in a group of four or five during their three-day trip to a multicultural setting in Indonesia: Bali island, and documented the activities in vlogs. The students’ vlogs which were data of this study were analyzed by using a qualitative content analysis approach. The findings showed that the scavenger hunt task resulted in the students' learning on cultural knowledge, intercultural communication, intercultural adaptation, information technology, and soft skills. During the three-day program, the students could also use English in a meaningful way. The study presented the strengths, weaknesses, and recommendations of this study, as well as some ideas for further research.Keywords: culture learning, intercultural communication, EFL,scavenger hunt.